(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Water is a most abundant physical substance and transparent liquid on earth. The groundwater is major source of drinking water in India. But due to rapid increasing in population, industrialization, use of fertilizers and human made activities, it is highly polluted with different harmful contaminants. Therefore it is necessary that the quality of drinking water should be checked at regular intervals like during pre monsoon and post monsoon. In the present study the groundwater samples were collected from different location of Janjgir-Champa district (Chhattisgarh) during pre monsoon and post monsoon (2022). The water quality was analyzed by different physical and chemical parameters such as PH, Total alkalinity, Total Dissolved solids (TDS), Total hardness, Chloride, Iron, Sulphate, Floride, Nitrate, DO, BOD. The results were compared with drinking water standards of Indian and World Health Organization (WHO). From the experiment it was found that the ground water samples is not polluted and can be used for drinking irrigation and domestic.